Pengaruh self-efficacy dan kualitas sumber daya manusia terhadap kepuasan kerja pegawai kantor camat Langsa lama - Sindy Yulia Rizki; Erni Junaida; Dhian Rosalina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of self-efficacy and human resource quality on job satisfaction of employees at the Langsa Lama Subdistrict Office. The research population consists of 43 employees. The sample used in this study is a saturated sample, where the entire population is used as the sample. Data collection was carried out using a questionnaire with measurements based on a Likert scale, and the data was processed statistically using multiple linear regression analysis with the equation Y = 2.795 + 0.106X1 + 0.038X2. The results show that, simultaneously, self-efficacy and human resource quality have a positive and significant effect on job satisfaction of employees at the Langsa Lama Subdistrict Office.